Confined space synthesis of fully alloyed and sinter-resistant AuPd nanoparticles encapsulated in porous silica - Samanta, Anupam; Rajesh, Thattarathody; Devi, R. Nandini (Journal of Materials Chemistry A, 2014)
Facile synthesis of highly sinter-resistant silica encapsulated Au-Pd alloy nanocatalysts with average particle size stabilized at similar to 4.5 nm even after calcination at 750 degrees C temperature is reported. The synthesis was achieved by utilizing thiol protected ultra small clusters of Au and Pd as precursors for silica encapsulation. The presence of intimate mixtures of the clusters within silica encapsulation ensures the formation of fully alloyed nanoparticles at high temperatures, at the same time controlling further growth and sintering. At optimum alloy compositions, these catalysts showed high catalytic activity for CO oxidation displaying low light-off temperatures.